Analysis of the Influence of Social Media Use on Consumer Behavior in Indonesia - Reina A. Hadikusumo; Rahmat Saleh; Tiago Costa (Journal of Loomingulisus ja Innovatsioon, 2025)
In recent years, social media has emerged as a powerful tool that shapes consumer behavior globally, especially in emerging markets like Indonesia. The growing prevalence of social media platforms has transformed the way consumers make purchasing decisions, engage with brands, and share their experiences. Despite the widespread use of social media in Indonesia, its specific influence on consumer behavior remains underexplored in academic research. This study aims to analyze the impact of social media use on consumer behavior in Indonesia. Specifically, it investigates how social media affects consumers' purchasing decisions, brand perception, and online shopping habits. A mixed-methods approach was used for this research. A survey was conducted with 500 Indonesian consumers who actively engage with social media platforms. The data collected were analyzed using descriptive and inferential statistical techniques, including regression analysis, to assess the relationship between social media usage and consumer behavior. The findings indicate a significant positive relationship between social media use and consumer purchasing decisions. Consumers who frequently engage with brand-related content on platforms like Instagram, Facebook, and Twitter tend to have higher brand recall and are more likely to make purchases based on recommendations from influencers or online ads. Social media plays a pivotal role in shaping consumer behavior in Indonesia, influencing both direct and indirect purchasing decisions.